Review on the Simulation of Cooperative Caching Schemes for MANETs - González-Cañete, Francisco Javier; Casilari-Pérez, Eduardo (My University, 2014)
In this paper, a review of the main simulation parameters utilized to evaluate the performance of cooperative caching schemes in Mobile Ad Hoc Networks is presented. Firstly, a taxonomy of twenty five caching schemes proposed in the literature about Mobile Ad Hoc Networks is defined. Those caching schemes are briefly described in order to illustrate their basis and fundamentals. The review takes into consideration the utilized network simulator, the wireless connection standard, the propagation model and routing protocol, the employed simulation area and number of data servers, the number of mobile devices and their coverage area, the mobility model, the number of documents in the network, the replacement policy and cache size, the mean time between requests, the document popularity distribution, the TTL (Time To Live) of the documents and the simulation time. Those simulation parameters have been compared among the evaluation of the studied cooperative caching schemes in order to obtain the most common utilized values. This work will allow to compare the performance of the proposed cooperative caching schemes using a common simulation environment.
Keywords: Sistemas de comunicaciones móviles; Mobile Ad hoc networks; Cooperative caching; Performance evaluation